Disentangling Justice Needs, Equality or Merit? On the Situation-Dependency of Distributive Justice - Gilgen, Sandra (Gesellschaftsanalyse, 2022)
What is fair? The choice of an allocation norm, whether it be need, merit or equality, can either foster cooperation or conflict. Because of the general irreconcilability of these principles of justice, people are forced to make complex trade-offs when allocating resources. The resulting decisions are shaped by individual factors and context, but also the situation in which an allocation problem arises. Addressing these three levels simultaneously and taking the inherent interdependency of outcomes into consideration, this book adheres to a mechanism-based approach. Its findings support a functionalist perspective on distributive justice, highlighting the inherent relevance of the relational structure for the choice of allocation norms.